Retrofitting of flourescent lamp with light emitting diode (LED) in IIUM main library for better energy efficiency - Maikano, Ahmad Abdullahi (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Global overall energy consumption is rising. Along with it, a relative contribution is lighting energy. While existing light sources are reaching their limit of performance, LED-based light sources are however offering the potential to meet energy saving targets with their improving performance. In most buildings, the dominant light source is the fluorescent lamp. Although it is energy efficient, the total energy it consumed is still significant, especially more so for public institutional buildings in Malaysia. This thesis studied the application of linear LED replacement tubes as the alternative retrofitting energy efficient solution to the existing fluorescent tubes in the IIUM Main Library. The study assessed LED's potential to reduce energy consumption and consequently, the electricity bill but with no reduced performance. The methodology used the data collection technique through physical walk-through audit and an observational survey of the existing lighting situation. The survey collected energy consumption data by the current light setting and was compared with the potential energy savings to be gained by installing the proposed LED retrofit. Using the Lighting Power Density (LPD) calculation methods from ASHRAE and IESNA, a recommended lighting level and cost analysis were undertaken. With the LED retrofit, the recommended lighting levels were established, and an annual savings of 33% was predicted in the library building. The cost analysis also projected a return on investment period of less than two years after replacing the existing fluorescent bulbs with the energy efficient LED tubes. It is hoped that the management of IIUM will have a basis to expand the study for the effective integration of energy efficient LED technology in its entire buildings & campuses to maximize the prospective financial savings.